Manajemen Program Study Visit dalam Menumbuhkan Dimensi Kreatif, Bernalar Kritis, dan Karakter Islami pada Anak Usia Dini - Imam Tobroni; Suratiyah; Nasrulloh; Miftahunangim (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is qualitative research that aims to describe the management process of the Study Visit program in fostering creative and critical thinking dimensions in children at RA Masithoh Bantar Wanareja Cilacap. The type of research used is qualitative descriptive. Research data were collected through interview, observation, and documentation techniques, and then analyzed using inductive data analysis techniques. Based on the research results, it is known that there are four steps in managing the Study Visit program at RA Masithoh Bantar Wanareja Cilacap, namely: (1) planning the Study Visit program, (2) organizing the Study Visit program, (3) implementing the Study Visit program, and (4) evaluating obstacles in the implementation of the Study Visit program to foster creative and critical thinking dimensions in early childhood. The Study Visit Program not only supports the development of children's creativity and critical reasoning abilities, but also helps instill Islamic values through habituating discipline, politeness, responsibility, and gratitude in experience-based learning activities. Thus, the Study Visit program can become one of the effective contextual learning strategies for early childhood. The limitation of this study lies in the research scope, which is limited to one institution, as well as the use of a qualitative approach. Future research is suggested to involve a wider sample and use mixed methods to obtain a more comprehensive picture of the effectiveness of the Study Visit program for early childhood.